Kapabilitas Lembaga Legislatif dalam Menjalankan Mekanisme Check and Balances Pasca Perubahan Undang-Undang Dasar 1945 - Utami, Iftitah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The main problems in this study are: how the authority of the legislature in carrying out the mechanism of checks and balances, and how the comparison of the capabilities of the legislature before and after the amendment of the 1945 Constitution (UUD). The purpose of this study is to analyze the authority of the legislature in maintaining the balance of power between state institutions, as well as assessing changes in the capabilities of the legislature after the amendment of the 1945 Constitution. This research uses normative juridical method, which is research based on literature study and analysis of relevant laws and regulations. The results show that the mechanism of checks and balances after the amendment of the 1945 Constitution causes the relationship between state institutions to become more complex, but at the same time strengthens government stability. This reflects the dynamics of democracy which takes time to form mature institutional procedures and habits that are acceptable to society, as happens in countries with established democracies. The conclusion of this study is that after the amendment of the 1945 Constitution, the position, duties and authority of the DPR (and DPRD) have changed significantly. Before the amendment, the President had full authority in the formation of laws. However, after the amendment, this authority was transferred to the DPR as the holder of legislative power. The President only has a role in ratifying draft laws that have been discussed with the DPR. This change strengthens the political and juridical position of the DPR, and increases its role in maintaining a system of control and balance in the administration of government.